The correlation of husband’s assistance with the risk of postpartum blues in postpartum mothers - Nadia Widiyanti; Dwi Astuti; Ana Zumrotun Nisak (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: The postpartum period is a very important period of physical and psychological adaptation for mothers after giving birth. One psychological disorder is postpartum blues or baby blues. One important intervention in reducing the risk of postpartum blues is support and assistance from the husband. Purpose: To determine the correlation of husband assistance on the risk of postpartum blues in postpartum mothers. Method: This study is a quantitative study using a correlational analytical model. The population in this study consisted of all mothers who gave birth at the Fita Ari Murtini Bae Kudus Midwife Practice (PMB) between September and November 2025, totalling 90 mothers. The sample size was calculated using the Slovin formula, resulting in a sample size of 74 mothers. The test used in this study was the chi-square test. Results: Respondents who were accompanied by their husbands in the good category numbered 48 (64.9%) respondents, respondents who were not depressed numbered 51 (68.9%) compared to those who experienced postpartum depression, namely 23 (31.1%). Conclusion: There is a relationship between spousal support and the occurrence of postpartum depression blues with a p-value of 0.002. The odds ratio (OR) value of 5.056 means that respondents who received spousal support were five times less likely to be depressed than those who received less spousal support. Suggestion: Other researchers investigate other factors that influence the occurrence of postpartum blues, such as family support other than the husband, socioeconomic factors, and the mother's psychological condition before giving birth.